Analysis of Social and Environmental Impact of the Existence of PT Citra Palu Mineral (CPM) Gold Mine on the Community in Poboya Village - Maulana, Alif; Usman, Rudy; Mustamin, Mustamin; Zahra, Femilia (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the social, economic, and environmental impacts of PT Citra Palu Minerals (CPM) mining activities on the surrounding communities in Poboya Village, and to evaluate the extent to which the company implements environmental accounting in its practices and reporting. Using a qualitative, case study-based approach, this study combines in-depth interviews, field observations, and analysis of company documents, particularly CPM's sustainability report. The results indicate that mining activities have transformed the livelihood structure of local communities, from previously dependent on the agricultural sector and traditional activities to dependent on the mining industry. However, promised employment opportunities have not been fully absorbed due to limited education and skills of local communities, leading to demands for a Community Mining Area (WPR) as a form of economic resistance and survival strategy. Field findings also revealed serious complaints regarding dust pollution and declining river water quality, which have prompted the community to switch to using drilled wells as an alternative water source. Although CPM's sustainability report lists health, reclamation, and environmental management programs, the community believes that the real impact on quality of life has not been fully realized. From an environmental accounting perspective, the company has recorded an environmental budget, but the information presented does not comprehensively reflect the effectiveness of its ecological impact control. This research confirms that the sustainability of the mining industry requires integration between ecological accountability, reporting transparency, and community involvement as the main actors in the sustainable development process.